HUBUNGAN STATUS PEKERJAAN IBU DAN KECUKUPAN ENERGI DENGAN STATUS GIZI BALITA DI WILAYAH PERKEBUNAN TEH PAGILARAN BATANG TAHUN 2018 - Hikmah Nurlita; Siti Fatimah Pradigdo; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2018)
Pagilaran plantation  is an area that becomes a resource of livelihood for the society in Keteleng village area. The amount of the employees are 1.127 people whose are separated as home office officer, tea factory worker, tea picker, and agrotourism management. The employees mostly are woman. This condition will affect the rolexof mothersxin takingxcarexof theirxchildren, it also affects the energy sufficiency and nutritional status of the under five year. The goal of this research was to know the correlation of mother’s employment and energy sufficiency to the nutritional status of the under five year around Pagilaran Plantation area in 2018. Thisxresearch used an analytic observational method with a cross-sectionalxapproach. The amount of research population was 478 hundred mothers who had under five year, then it was adjusted with the research criteria with the result 60 samples. Sampling method used simple random sampling. Research instrument used questionnaire, form recall 2 x 24 hours and weight scales. Thexresult data of the research were analyzed with chi-square and correlation test rank spearman. The result of the research showedxthat responden were mostly were not working. Most of the under five year intake were less than AKE, however most of the children had an ideal nutritional status (z-score -2 until 2). Data of the research were analyzed with statistic showedxthat there is no correlationxbetweenxthe mother’s employment statusxand energy sufficiency (p=0,454). Therexis no correlation betweenxenergy sufficiency and the nutritional status of the under five year (p=0,163). Mothers who had under five child should notice the supply of food for their under five year, so it would be matched to AKG.